THE CONSTITUTION IS A STRONG LEGAL FOUNDATION OF THE DEVELOPMENT OF THE NEW UZBEKISTAN - Aliyeva , Zuhra Bahodir qizi (Educational Research in Universal Sciences, 2024)
This article details the results of the referendum, how many voters participated, and the changes and additions to the Constitution.